Commuting Carless: A Qualitative Study of Transportation Challenges for Disadvantaged Job Seekers in Chicago, IL. Issue 6 (June 2022) - Coren, Chelsie; Lowe, Kate; Barajas, Jesus M.
Intersecting systems of land use and transportation access, employment opportunities, employer roles, and neighborhood dynamics shape commuting experiences among people of color and other marginalized communities, but how they do so is not well known. This study adopts a qualitative approach to identify understudied and interconnected factors in the transportation experiences of disadvantaged job seekers in Chicago, especially those identifying as Black who commute without cars. Majority Black job seekers in focus group discussions reported a complex web of transportation barriers to employment, including those related to geographic and schedule mismatches, resulting in lost opportunities and heavy commute burdens. Job seekers desire closer quality jobs and more coordination between employers and transit agencies. Respondents suggested that employers, who are sometimes biased toward hiring those with personal vehicles, are personally unaware of transportation experiences that the entry-level workforce faces. Findings showed that job access strategies for disadvantaged workers need broader understandings of lived—rather than solely modeled—job accessibility. Accessibility assessments will be overly optimistic without accounting for security concerns that exist in some locations and that disproportionately affect people of color. Although transportation improvements are vital, the findings showed that transportation strategies are insufficient without holistic strategies, such as equitable community and economic development.